Pharmacokinetics of Herb-Drug Interactions of Plumbagin and Tazemetostat in Rats by UPLC-MS/MS - Li H; Wang YJ; Geng XN; Kang YR; Wang YL; Qiu XJ (Dove Medical Press, 2022)
Heng Li,1 Ying-Jie Wang,1 Xiao-Nan Geng,1 Yao-Ren Kang,1 Yi-Lin Wang,1 Xiang-Jun Qiu1,2 1Department of Pharmacy, School of Basic Medical Sciences, Henan University of Science and Technology, Luoyang, 471023, People's Republic of China; 2Functional Experiment Teaching Center, School of Basic Medical Sciences, Henan University of Science and Technology, Luoyang, 471023, People's Republic of ChinaCorrespondence: Xiang-Jun Qiu, Functional Experiment Teaching Center, School of Basic Medical Sciences, Henan University of Science and Technology, 263 Kaiyuan Avenue, Luoyang, 471023, Henan, People's Republic of China, Email lyxiangjun@126.comObjective: A sensitive and rapid UPLC-MS/MS method for determination of tazemetostat in rat plasma was developed, and the pharmacokinetics of herb-drug interactions (HDIs) of plumbagin (PLB) and tazemetostat was investigated.Methods: After the rat plasma samples were precipitated by acetonitrile, tazemetostat and verubecestat (ISTD) were detected. Gradient elution was performed with 0.1% formic acid and acetonitrile as mobile phases. The multi-reaction monitoring was used with ESI+ source, and the ion pairs for tazemetostat and ISTD were m/z 573.12→ 135.99 and m/z 410.10→ 124.00, respectively. 12 SD rats were randomly divided into the control group and the experimental group, 6 rats in each group. The rats in the experimental group were given PLB 100 mg/kg by gavage once a day for 7 consecutive days. The rats in the control group were given the same amount of 0.1% sodium carboxymethyl cellulose solution by gavage once a day for 7 consecutive days. At the seventh day, tazemetostat (80 mg/kg) was given and the blood was collected at different time points. The main parameters of pharmacokinetics were calculated and the herb-drug interactions (HDIs) were evaluated.Results: In the calibrated range of 1- 1000 ng/mL, tazemetostat had a good linearity. The extraction recovery was more than 84%, and the RSD of intra-batch and inter-batch precision were both less than 15%. The Cmax of tazemetostat in the experimental group was 32.48% higher than that in the control group, and the AUC(0-t) and AUC(0−∞) of tazemetostat in the experimental group were 46.24% and 46.67% higher than that in the control group, respectively, and the t1/2 was prolonged from 10.56 h to 11.73 h.Conclusion: A simple, rapid and sensitive UPLC-MS/MS method for the determination of tazemetostat in rat plasma was established. PLB can inhibit the metabolism of tazemetostat and increase the plasma exposure of tazemetostat in rats.Keywords: plumbagin, tazemetostat, UPLC-MS/MS, pharmacokinetics, herb-drug interactions